IDENTITY AND CULTURE OF ISRAELI CHRISTIANS IN THE FACE OF ISLAMIC RESURGENCE; CULTURAL DISTINCTIVENESS OF A MINORITY WITHIN A MINORITY - Farah, Rima (The levantine review, 2013)
This paper examines how Israeli Christians perceive their cultural position between Jewish and Muslim identities in Israel. The study primarily relates to the cultural differences between Christians and Muslims, and to the relations between them in mixed villages and towns. It focuses on how the sense of identity and the cultural aspects, combined with the rise of the Islamic identity and the change of Arab society’s structure has affected the peaceful coexistence between Christians and Muslims. Lastly, the research addresses the 1999 Christian-Muslim riots (Shihab al-Din Events) in Nazareth over plans to construct a Mosque in front of the Church of Annunciation.